Cara Membangun Bisnis Tim - Yohana Andriani; Suwarni Suwarni; Ahmad Soleh; Tito Irwanto; M. Rahman Febliansa (Jurnal Dehasen Untuk Negeri, 2023)
Building a business is one of the efforts made by business people in starting or maintaining their business in the midst of intense competition. Not only that, running a business is an option for some people as a way to fulfill their daily needs, whether they already have a main job or those who don't have a job. In doing business, there are various fields that can be run, business people usually and should adapt to the needs of the market at that time or according to their expertise or even hobbies. Given that if you build a business without adjusting things like that, you will have difficulty running your business. In building a business, of course, you must be able to build a good team so that the business that is built can develop well